AC loss in YBCO coated conductors at high dB/dt measured using a spinning magnet calorimeter (stator testbed environment). (September 2017) - Murphy, J.P.; Gheorghiu, N.N.; Bullard, T.; Haugan, T.; Sumption, M.D.; Majoros, M.; Collings, E.W.
Highlights: The development of a new device for measuring AC losses in HTS conductors at high dB / dt  ∗  B is described. This device is able to subject a sample to both high B and high dB/dt, reaching 270 T/s at a B of 0.566 T. A comparison of measurements made with this machine to those of a more conventional loss device made. The field spatial and temporal profiles are described, which mimic those of a generator. Abstract: A new facility for the measurement of AC loss in superconductors at high dB/dt has been developed. The test device has a spinning rotor consisting of permanent magnets arranged in a Halbach array; the sample, positioned outside of this, is exposed to a time varying AC field with a peak radial field of 0.566 T. At a rotor speed of 3600 RPM the frequency of the AC field is 240 Hz, the radial dB/dt is 543 T/s and the tangential dB/dt is 249 T/s. Loss is measured using nitrogen boiloff from a double wall calorimeter feeding a gas flow meter. The system is calibrated using power from a known resistor. YBCO tape losses were measured in the new device and compared to the results from a solenoidal magnet AC loss system measurement of the same samples (in this latter case measurements were limited to a field of amplitude 0.1 T and a dB/dt of 100 T/s). Solenoidal magnet system AC loss measurements taken on a YBCO sample agreed with the Brandt loss expression associated with a 0–0.1 T Ic of 128 A. Subsequently, losses for two more YBCO tapes nominally identical to the first were individually measured in this spinning magnet calorimeter (SMC) machine with a Bmax of 0.566 T and dB/dt of up to 272 T/s. The losses, compared to a simplified version of the Brandt expression, were consistent with the average Ic expected for the tape in the 0–0.5 T range at 77 K. The eddy current contribution was consistent with a 77 K residual resistance ratio, RR, of 4.0. The SMC results for these samples agreed to within 5%. Good agreement was also obtained between the results of the SMC AC loss measurement and the solenoidal magnet AC loss measurement on the same samples.